INVENTARISASI ANGGREK HUTAN DI TAHURA GUNUNG TUMPA - Efendy Renaldo Karoy; Reynold P. Kainde; Euis F. Pangemanan (COCOS, 2022)
ABSTRACT Taxonomically, orchids belong to the Orchidaceae family, one of the taxa with the most species and habitat diversity. In Indonesia there are about 6,000 species of orchids or about 23% of the 26,000 species of orchids in the world. This study aims to conduct an inventory of forest orchid species and analyze the diversity index of orchid species in the nature conservation area of TAHURA Gunung Tumpa. This research was carried out in May 2021. Data collection was carried out using an exploratory method by following 8 transect lines based on the 8 cardinal directions. Data collection for orchids was carried out from morning to evening at 07:00 - 16:00 WITA. The resulting inventory of forest orchid species in TAHURA Gunung Tumpa found 184 individuals consisting of 8 orchid species. There were 3 terrestrial orchids (Nervilia aragoana, Calanthe triplicata, Eulophia spectabilis) and 5 epiphytic orchids (Phalaenopsis amabilis, Pholidota imbricata, Dendrobium sp, Diplocaulobium sp, Eria iridifolia). The orchid species diversity index at TAHURA Gunung Tumpa falls in the medium category with a value of H' = 1.29